The study of the effect of intake valve timing on engine using cylinder deactivation technique via simulation - Zainal Abidin, S. F.; Muhamad Said, M. F.; Abdul Latiff, Z.; Zahari, I.; Said, M. (Penerbit Universiti Teknologi Malaysia Press, 2015)
There are many technologies that being developed to increase the efficiency of internal combustion engines as well as reducing their fuel consumption. In this paper, the main area of focus is on cylinder deactivation (CDA) technology. CDA is mostly being applied on multi cylinders engines. CDA has the advantage to improve fuel consumption by reducing pumping losses at part load engine conditions. Here, the application of CDA on 1.6L four cylinders gasoline engine is studied. One-dimensional (1D) engine modeling work is performed to investigate the effect of intake valve strategy on engine performance with CDA. 1D engine model is constructed based on the 1.6L actual engine geometries. The model is simulated at various engine speeds at full load conditions. The simulated results show that the constructed model is well correlated to measured data. This correlated model is then used to investigate the CDA application at part load conditions. Also, the effects on the in-cylinder combustion as well as pumping losses are presented. The study shows that the effect of intake valve strategy is very significant on engine performance. Pumping losses is found to be reduced, thus improve fuel consumption and engine efficiency.